(untitled) (Revista Brasileira de História da Educação, 2011)
SCHMIDT, Maria Auxiliadora; BARCA, Isabel; MARTINS, Estevaão de Rezende (Org.). JÃ¶rn RÃ¼sen e o ensino de história. Curitiba: Ed.UFPR, 2010